The Transmission Channels of Corruption and Economic Growth in Nigeria from 1987 to 2017 - Lawal, Yusuf Oke; George, Emmanuel Oladapo (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
While there is a plethora of empirical studies on the relationship between corruption and economic growth, the transmission channels through which corruption affects economic growth have not been well documented in the literature. This study therefore investigates the effects of corruption on economic growth in Nigeria especially with respect to the transmission channels using Seemingly Unrelated Regression (SUR) model (SUR). Secondary time series data sourced from Transparency International, Central Bank of Nigeria (CBN) Statistical Bulletin and World Development Indicators (WDI) for the periods of 1987 to 2017 were used. The result reveals that corruption affects economic growth through investment (GFCF), human capital (HC) and ICT expenditure channel and recommends that government should strengthen the anti-corruption agencies in order to holistically fight corruption at all levels. Keywords: Corruption, economic growth and seemingly unrelated regression model.